Hydroxychloroquine to prevent SARS-CoV-2 infection among healthcare workers: early termination of a phase 3, randomised, open-label, controlled clinical trial - Llanos-Cuentas, Alejandro (2023)
Objective: To assess the effectiveness and safety of hydroxychloroquine (HCQ) prophylaxis for the prevention of SARS-CoV-2 infection in healthcare workers (HCW) on duty during the COVID-19 pandemic. Results: A total of 68 HCWs met the eligibility criteria were randomly allocated to receive HCQ (n = 36) or not (n = 32). There were no significant differences between groups in respects to age, gender, or medical history. Eight participants met the primary efficacy endpoint of SAR-CoV-2 infection during the study period; there was no difference in incidence of SARS-CoV-2 infections between both study arms (HCQ: 5 vs Control: 3, p = 0.538). The relative risk of SARS-CoV-2 infection in the HCQ arm was 1.69 compared to the control group (95%CI 0.41–7.11, p = 0.463); due to poor participant accrual, the resulting statistical power of the primary efficacy outcome was 11.54%. No serious adverse events occurred; however, two (2/36, 5.6%) participants no longer wished to participate in the study and withdrew consent due to recurring grade 1 and 2 adverse events. Trial registration: ClinicalTrials.gov ID: NCT04414241. (Registered on June 4, 2020).